Health-related quality of life-based definition of remission from depression among primary care patients - Riihimäki, Kirsi; Sintonen, Harri; Vuorilehto, Maria; Isometsä, Erkki (Frontiers in Psychiatry, 2023)
Background: Depression undermines health-related quality of life (HRQoL). Remission is the central aim of all treatments for depression, but the degree of remission necessary for depressive patients’ HRQoL to correspond to the normal range of the general population remains unknown. Methods: The Vantaa Primary Care Depression Study prospectively followed-up a screening-based cohort of depressive primary care patients for five years. The Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) was used to diagnose major depressive disorder. HRQoL was measured by the generic 15D instrument at baseline and at five years (N=106, 77% of baseline patients), and compared with the 15D distribution of an age-standardized general population sample from the Finnish Health 2011 Survey (N=3707). Receiver operating characteristic analyses determined the optimal Hamilton Depression Rating Scale (HAMD), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) cut-offs for remission, using the 15D score as the construct validator. Remission was defined as the score at which HRQoL reached the general population range (minimum mean -1 SD). As age may influence HRQoL, patients older and younger than the median 52 years were investigated separately. Results: For HAMD, the optimal cut-off point score was 8.5, for BDI 10.5, and for BAI 11.5. The differences between the findings of the younger and older patients were small. Limitations: Cross-sectional analysis, small number of patients in the cohort. Conclusions: Depressive primary care patients’ HRQoL reaches the normal variation range of the general population when their depression and anxiety scores reach the conventional clinical cut-offs for remission.